Dupilumab improve acquired reactive perforating collagenosis characterized by type 2 inflammation - Liu, Ben; Wu, Yibei; Wu, Xiaoyan; Zhong, Xinyu; Xue, Ruzeng; Zhang, Zhenying (Frontiers in Immunology, 2023)
Background: Acquired reactive perforating collagenosis (ARPC) is a clinically challenging disease with an unclear pathogenesis. Objective:To evaluate the efficacy and safety of dupilumab for the treatment of ARPC, and analyze the expression of type 2 inflammation-related molecules in ARPC lesions. Methods: This retrospective cohort study included 20 patients with ARPC; 10 received dupilumab and 10 received conventional therapy. The efficacy and safety of dupilumab were evaluated at 12 weeks. Immunohistochemical and immunofluorescence analyses of T- and B-cell markers, and type 2 inflammation-related cytokines, were performed on skin samples from ARPC patients, atopic dermatitis (AD) patients, and healthy controls. Results: Significantly more patients showed improvements in the Investigator Global Assessment score (100% vs. 0%; p < 0.0001) and itching (90%/8.33%, P =.001) in the dupilumab group compared to the conventional group at 12 weeks. There were no adverse effects in the dupilumab group. The ARPC lesions showed enhanced dermal infiltration of CD3+ T-cells, with a predominance of Th2 cells, similar to AD lesions. IL-4 and IL-13 were co-localized with GATA3 in ARPC lesions. Conclusions: Dupilumab improved ARPC charaterized with type 2 inflammation.